The Persian Self-Report Version of the Antisocial Process Screening Device (APSD-P): A Psychometric Evaluation - Ebrahimi, Ali; Elhami Athar, Mojtaba; Darvishi, Mona; Colins, Olivier F. (Frontiers in Psychiatry, 2021)
The self-report version of the Antisocial Process Screening Device (APSD) is a commonly used tool for assessing psychopathic traits in youth. This is the first study designed to examine the factor structure, internal consistency, and convergent validity of the Persian APSD-SR in a sample of 675 school-attending youth in Iran (46% girls; M age = 16.35). Confirmatory factor analysis supported a modified three-factor model, with items loading on narcissism, callous-unemotional, and impulsivity dimensions, which was invariant across gender. Notwithstanding that the internal consistency of some APSD scores was unsatisfactory, the APSD total and dimension scores showed the expected relations with external correlates (e.g., conduct problems, aggression, and low prosocial behavior), supporting the validity of the interpretation of the APSD scores. The findings showed that APSD is a useful tool for assessing psychopathic traits in Iranian adolescents and may spark research on adolescent psychopathy in mental health and forensic settings).